Automated calibration of a parametric spring reverb model - Gamper, Hannes; Parker, Julian; Välimäki, Vesa (Proceedings of the 14th International Conference on Digital Audio Effects (DAFx), 2011)
The calibration of a digital spring reverberator model is crucial for the authenticity and quality of the sound produced by the model. In this paper, an automated calibration of the model parameters is proposed, by analysing the spectrogram, the energy decay curve, the spectrum, and the autocorrelation of the time signal and spectrogram. A visual inspection of the spectrograms as well as a comparison of sound samples proves the approach to be successful for estimating the parameters of reverberators with one, two and three springs. This indicates that the proposed method is a viable alternative to manual calibration of spring reverberator models.